Pengaruh Literasi Keuangan Syariah Terhadap Keputusan Memilih Asuransi Syariah: Analisis Tingkat Pemahaman Dan Kesadaran Finansial - Azri, Ahmad Danil; Rezki, Muhammad; Purwanto, Muhammad Aji (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2024)
This research examines and discusses how sharia financial literacy influences the decision to choose sharia insurance. In today’s modern era, the level of understanding of sharia finance is very important in determining the insurance you want to use and reducing risks that affect financial losses. A good understanding of finances can improve the quality of decision making to achieve prosperity. The aim of this research is to analyze the influenceof sharia financial literacy on the choice of sharia insurance. This research involved a sampel of 48 stundents of the sharia economics study program at the Bengkalis State Islamic College. The results of this research show that, with sharia financia literacy, students feel able to understand sharia insurance as financial protection. Students also feel that sharia financial literacy provides a level of understanding of sharia insurance. Based on this, it can be seen that sharia financial literacy has a significant impact on the choice of sharia insurance and fosters confidence in the use of sharia financial product for better risk management.